2000
DOI: 10.1038/82751
|View full text |Cite
|
Sign up to set email alerts
|

OmpA targets dendritic cells, induces their maturation and delivers antigen into the MHC class I presentation pathway

Abstract: We analyzed the interaction between a bacterial cell wall protein and dendritic cells (DCs). Outer membrane protein A from Klebsiella pneumoniae (kpOmpA) specifically bound to professional antigen presenting cells and was endocytosed by immature DCs via a receptor-dependent mechanism. kpOmpA signaled through Toll-like receptor 2, induced DCs to produce interleukin 12 and induced maturation of DCs. Whole antigen that was coupled to kpOmpA and injected into mice was taken up by DCs and delivered to the conventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
133
1
1

Year Published

2002
2002
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 199 publications
(145 citation statements)
references
References 53 publications
(35 reference statements)
10
133
1
1
Order By: Relevance
“…These mechanisms may be employed to load exogenous antigen on MHC class I molecules in vitro and potentially also in vivo. Recently, Jeannin et al 117 showed that whole antigen coupled to a Klebsiella pneumoniae protein (kpOmpA ) specifically bound to a receptor on professional APCs and resulted in the delivery of antigen into the MHC class I presentation pathway. Simultaneous immunization with kpOmpA coupled to ovalbumin resulted in protection against a tumor challenge with ovalbumin -expressing tumor cells.…”
Section: Improving the Efficiency Of Cross -Primingmentioning
confidence: 99%
“…These mechanisms may be employed to load exogenous antigen on MHC class I molecules in vitro and potentially also in vivo. Recently, Jeannin et al 117 showed that whole antigen coupled to a Klebsiella pneumoniae protein (kpOmpA ) specifically bound to a receptor on professional APCs and resulted in the delivery of antigen into the MHC class I presentation pathway. Simultaneous immunization with kpOmpA coupled to ovalbumin resulted in protection against a tumor challenge with ovalbumin -expressing tumor cells.…”
Section: Improving the Efficiency Of Cross -Primingmentioning
confidence: 99%
“…Additionally, we set out to elucidate which mechanisms are responsible for these processes. To mimic a bacterial infection, DC were matured by a membrane fraction of K. pneumoniae (FMKp), which is a lysate of the outer membrane fraction of K. pneumoniae containing the DC-triggering agents LPS and outer membrane protein A (OmpA), which signal trough TLR4 and TLR2, respectively [20]. For its proven additional effect on upregulation of costimulatory molecules and modulation of cytokine secretion, IFN-g was added to the FMKp maturation cocktail [21].…”
Section: Introductionmentioning
confidence: 99%
“…The gene encoding the P40 from K. pneumoniae was provided by the Centre d'Immunologie Pierre Fabre (CIPF, Saint Julien en Genevois, France). [18][19][20][21] The human CD40L cDNA was purchased from InvivoGen (Cayla, Toulouse, France). The gene encoding the HN of the NDV was derived from plasmid p36/7-HN.…”
Section: Adenoviral Vectorsmentioning
confidence: 99%
“…18,19 P40 binds TLR2 on the surface of antigen-presenting cells (DCs and macrophages) and induces the phenotypic maturation of DCs, [18][19][20] secretion of interleukin (IL)-12 and the inflammatory cytokines IL-6, IL-8 and tumor necrosis factor (TNF)-a. P40 mixed with a tumor antigen peptide was shown to elicit tumor-specific CTL responses and to significantly delay the growth of B16F10 melanoma tumors implanted at the time of immunization. 21 Flagellin is the main component of the bacterial flagella and induces DC maturation and chemokine secretion by activating NF-kB through their interaction with TLR5.…”
Section: Introductionmentioning
confidence: 99%